Frost and leaf‐size gradients in forests: global patterns and experimental evidence. Issue 2 (16th May 2018) - Lusk, Christopher H.; Clearwater, Michael J.; Laughlin, Daniel C.; Harrison, Sandy P.; Prentice, Iain Colin; Nordenstahl, Marisa; Smith, Benjamin
Summary: Explanations of leaf size variation commonly focus on water availability, yet leaf size also varies with latitude and elevation in environments where water is not strongly limiting. We provide the first conclusive test of a prediction of leaf energy balance theory that may explain this pattern: large leaves are more vulnerable to night‐time chilling, because their thick boundary layers impede convective exchange with the surrounding air. Seedlings of 15 New Zealand evergreens spanning 12‐fold variation in leaf width were exposed to clear night skies, and leaf temperatures were measured with thermocouples. We then used a global dataset to assess several climate variables as predictors of leaf size in forest assemblages. Leaf minus air temperature was strongly correlated with leaf width, ranging from −0.9 to −3.2°C in the smallest‐ and largest‐leaved species, respectively. Mean annual temperature and frost‐free period were good predictors of evergreen angiosperm leaf size in forest assemblages, but no climate variable predicted deciduous leaf size. Although winter deciduousness makes large leaves possible in strongly seasonal climates, large‐leaved evergreens are largely confined to frost‐free climates because of their susceptibility to radiative cooling. Evergreen leaf size data can therefore be used to enhance vegetation models, and to infer palaeotemperatures from fossil leaf assemblages.